Despotic leadership and employee's outcomes: Mediating effect of impression management - Ghulam Rasool; Saima Naseer; Fauzia Syed; Israr Ahmed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
This article aims at analyzing the mediating role of impression management in the relationship between despotic leadership and the employees. outcomes which include organizational career growth, job performance and creativity. Using self motive theory, we hypothesize that despotic leaders might force individuals, out of fear or out of personal self-interests, to engage in impression management techniques thus promoting high career growth, job performance and creativity. Field survey was used for the collection of data at three different time intervals containing a time lag of one and a half month between each time wave from respondents serving at different positions in public sector organization and their peers. Structural Equation Modeling (SEM) technique was used to test and verify the hypothesis of the study. The results prove the mediating role of impression management in the relationship between despotic leadership and the employee.s outcomes. The study attempts to bridge a gap in the dark side of leadership through opening up a sunny side of a negative leader that how and why a dark leader such as despotic leader might produce positive outcomes for followers.
Keywords: 330; despotic leadership; impression management; organizational career growth; job performance; employee creativity; self-motives